The Comparative Analysis of the Hiwalah Fatwa between Indonesia and Malaysia: دراسة المقارنة : الحوالة في ضوء فتوى الهيئة الشرعية الوطنية لمجلس العلماء الإندونيسي ولجنة الإفتاء بالولايات الفدرالية الماليزية - Risdayani, Risdayani; Bachtiar, Muhammad Harsya; Ahyarudin, Ahyarudin (Indonesian Journal of Islamic Economic Law, 2024)
The objective of this study is to examine the differences and similarities in the application and interpretation of the fatwa on hawalah contracts between the Indonesian Ulema Council and the Malaysian Fatwa Committee. The research methodology employed in this study is qualitative research, employing a comparative approach. Following the collection of data from fatwas, books, and other literature, the data is subjected to inductive analysis in order to yield the results of this study. The analysis of similarities and differences, as well as compatibility with Islamic law, conducted between the DSN-MUI fatwa and the Regional Mufti of Biscotuan's fatwa on hawalah has led to the following conclusions: DSN Fatwa No. 12/DSN-MUI/IV/2000: The aforementioned fatwa is in accordance with Shariah principles as it fulfils the elements and conditions of hawalah without an increase in rent or profit. Fatwa No. 58/DSN-MUI/V/2007: The aforementioned instrument is not fully compliant with Shariah principles because it allows for the imposition of fees in the context of a pending hawalah transaction, which may potentially lead to riba. In contrast, the Mufti of Persekutuan Province has issued a fatwa that is compatible with Shariah principles. This fatwa ensures that hawala transactions are only between two parties with a debt-to-debt relationship and that no fees are charged. Consequently, the instrument avoids the imposition of usury. In this context, the fatwa of the Pijapat Persekutuan Mufti is more rigorous in maintaining compliance with Sharia principles, particularly in preventing usury. Although Islamic financial institutions recognise hawalah as a practical necessity, they must exercise caution to ensure that they do not contravene the fundamental Shariah principle of prohibiting usury.